Bacteriological Study of Carbapenem and Aminoglycoside Resistance in Staphylococcus Aureus Recovered from Patient in Baghdad Province - Hajir Adil Anwar; Maliha Masaoud; Ahmed Salim (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: In population- and hospital-acquired infections, Staphylococcus aureus is one of the most powerful causative agents. Aminoglycosides are active bactericidal drugs and are frequently used to treat staphylococcal infections in conjunction with beta-lactams or glycopeptides. Staphylococcus aureus is immune to carbapenems and other beta-lactams A different mechanism that can lead to carbapenem resistance is the active expulsion of carbapenems from the periplasmic space after their entry, due to the high distribution of these bacteria that are now immune to other antibiotics, it has become more difficult to treat these drug-resistant strains. Materials and Methods: A total of 130 staph.aureus isolates were isolated from different clinical samples in some public & private hospitals in Baghdad city during the period from November to December 2019. Bacterial identification was done using conventional cultural & chemical methods & and VITEk 2 cards for identification (GP), while the minimum inhibitory concentration (MIC) testing was performed using disk diffusion & (AST-GP30) cards in VITEK 2 automated system. Results: By using disk duffusion test out of 130 of Staph.aureus isolate, 76(58.4%) were resistant to aminoglycosids antibiotics (gentamicin) while 29(22.3%) were resistant to carbapenem antibiotics (imipenem) The MIC of different antibiotics was performed on 26 isolates using (VITEK2AST-GP30) showed that 18(69.2%) were resistant to aminoglycosids antibiotics (gentamicin) while 26(100%) were resistant to carbapenem antibiotics (imipenem). Conclusion: The MIC of different antibiotics By using disk duffusion the Staph.aureus isolate resistant to gentamicin 76(58.4%) and 29(22.3%) were resistant to imipenem, while, by VITEK2AST-GP30 showed 18(69.2%) were resistant to gentamicin , while 26(100% were resistant to imipenem.